Corticosterone Levels, Heterophil/Lymphocyte Ratios and Growth Rates in Lohmann Indian River Chickens Raised under Monochromatic Blue Light - Astuti , P.; Al Fajar, B.; Mauludin, M.; Hana, A.; Airin, C. Mona; Sarmin, S.; Harimurti, S. (International Journal of Poultry Science, 2015)
Light intensity affects the growth rate of chickens. Previous research reported that blue light with a wavelength of 460 nm can increase the growth rate of chickens compared to green and red light. No reports have investigated whether the effects of 460-nm blue light remain even when the change in lighting is intermittent. This study therefore aimed to obtain more information about the effects of exposing chickens to 460-nm blue light with differing intensity levels. This study used roughly 2700 one-day-old Lohmann chickens raised at Wonokerto, Turi, in the Sleman District of Jogjakarta. The chickens were divided into 3 groups: a group without artificial lighting (the control), a group with intermittent blue lighting (with 12 h under monochromatic blue light) and a group with continuous monochromatic blue lighting. Blood samples were taken on days 1, 7, 14, 21 and 28. Then, the blood samples were separated into their plasma and serum components. The plasma was used to determine the numbers of heterophils and lymphocytes, while the serum was frozen to detect corticosterone levels using an enzyme-linked immunosorbent assay (ELISA). The results showed that exposure to the 460-nm wavelength blue light increased the body weights of chickens as measured at the 4th and 5th weeks. This increase started during the 3rd week (p0.05) except on day 14 (p